Simulation capacity building in rural Indian hospitals: a 1-year follow-up qualitative analysis. (14th August 2020) - Sheshadri, Veena; Wasserman, Isaac; Peters, Alexander W; Santhirapala, Vatshalan; Mitra, Shivani; Sandler, Simone; Svensson, Emma; Ljungman, David; George, Regi; Ambepu, Arundhathi; Krishnan, Jithendranath; Kataria, Raman; et al.
Abstract : Introduction: The benefits of simulation-based medical training are well described. The most effective way to plant and scale simulation training in rural locations remains undescribed. We sought to plant simulation training programmes for anaesthesia emergencies in two rural Indian hospitals. Methods: Two Indian consultant anaesthetists without experience in medical simulation underwent a 3-day course at the Boston Children's Hospital's (BCH) Simulator Program. They returned to their institutions and launched simulation programmes with an airway manikin and mock patient monitor. The 1-year experience was evaluated using individual, in-depth interviews of simulation facilitators. Three staff members (responsible for facilitating medical simulations over the prior year) at two rural hospitals in India were interviewed. None attended the BCH training; instead, they received on-the-job training from the BCH-trained, consultant anaesthetist colleagues. Results: Successes included organisational adoption of simulation training with exercises 1 year after the initial BCH-training, increased interdisciplinary teamwork and improved clinical competency in managing emergencies. Barriers to effective, local implementation of simulation programmes fell into three categories: time required to run simulations, fixed and rigid roles, and variable resources. Thematic improvement requests were for standardised resources to help train simulation facilitators and demonstrate to participants a well-run simulation, in addition to context-sensitive scenarios. Conclusion: An in-person training of simulation facilitators to promote medical simulation programmes in rural hospitals produced ongoing simulation programmes 1 year later. In order to make these programmes sustainable, however, increased investment in developing simulation facilitators is required. In particular, simulation facilitators must be prepared to formally train other simulation facilitators, too.